Detecting swine influenza A virus during fattening and at slaughter: implications for monitoring strategies in fattening herds - Pauline Deffner; Katrin Jankowitsch; Matthias Eddicks; Susanne Zöls; Mathias Ritzmann; Yury Zablotski; Robert Fux; Timm Harder; Kathrin Lillie – Jaschniski; Julia Stadler (Porcine Health Management, 2026)
Abstract Background Swine influenza A virus (swIAV) is a major contributor to respiratory disease in pigs and represents a One-Health concern. This study evaluated whether slaughterhouse sampling can complement or partially substitute on-farm monitoring by comparing slaughterhouse-derived sample specimens for swIAV detection and subtype characterization. Results Twenty-one pig farms in Germany were enrolled, and one batch of fatteners per farm was monitored longitudinally using pen-based oral fluids (OFs) at three predefined time points during fattening. In case of acute respiratory distress, tracheobronchial swabs (TBS) were collected from 15 affected pigs. At slaughter, 30 pigs per farm were sampled and tested for swIAV by qPCR, yielding OFs, nasal swabs before and after scalding (NS I/NS II), bronchial swabs (BS), lung tissue (LT), and serum. Overall, 18/21 farms (85.7%) were classified as swIAV-positive, with a seroprevalence of 92.4% in the study population. During fattening, swIAV-RNA was detected in OFs collected on-farm in 7/21 farms (33.3%) at least once, most frequently at the beginning of fattening. Among 15 farms with TBS sampling, swIAV-RNA was detected in 4 farms (26.7%). At slaughter, swIAV-RNA was detected in at least one matrix on 7/21 farms and in 74/540 pigs (13.7%). Detection probability at slaughter differed by specimen: lower respiratory tract samples showed higher detection rates and lower Ct-values than NS (BS: 9.7%, LT: 10.9%; NS: 6.3%). Diagnostic agreement between materials ranged from fair to moderate, highest between BS and LT (κ = 0.58; p < 0.001). Slaughterhouse OFs showed low sensitivity. From selected RT-qPCR-positive samples with Ct < 33, BS yielded the highest proportion of successfully subtyped samples. Subtypes HA-1 C.2.1 (H1avN1EA), HA-1 C.2.4 (H1avN2G), and HA-1B.1 (H1huN2G) were identified in 4/7 RT-qPCR-positive farms. Conclusion Despite longitudinal OF sampling during fattening and additional TBS collection during acute respiratory disease, swIAV-RNA was only detected in a subset of seropositive farms. Molecular detection at slaughter was likewise restricted, whereas serology substantially improved herd-level identification. Among PCR-based sample types in slaughter pigs, BS demonstrated the highest diagnostic yield and suitability for subtype characterization. Even combined, on-farm and slaughterhouse RT-qPCR approaches remained constrained by the transient nature of swIAV shedding. Slaughterhouse sampling therefore complements—but does not replace—structured on-farm investigations for comprehensive surveillance.